2019
DOI: 10.23968/2305-3488.2019.24.1.3-9
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Wastewater Treatment Efficiency in Pneumohydraulic Flotators

Abstract: Аннотация Приведены основные параметры, влияющие на эффективность флотационной очистки воды: размеры генерируемых пузырьков газов и их количество. Кратко рассмотрены основные способы аэрации, используемые для флотационной очистки воды. Особое внимание уделено пневмогидравлической флотации. Рассмотрены два способа повышения эффективности очистки воды в пневмогидравлических флотаторах. Первый заключается в подаче воздуха перед насосом, а второй-в применении диспергирующих устройств. Описана лабораторная установк… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 1 publication
0
4
0
1
Order By: Relevance
“…The pneumohydraulic method is realized by the transmission of an air-water mixture through the aerator. Previous works [11,55,[65][66][67][68] showed that the supply of the air before the pump is the most efficient method to generate microbubbles. This aeration method is shown schematically in Figure 6.…”
Section: Pneumohydraulic Flotationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pneumohydraulic method is realized by the transmission of an air-water mixture through the aerator. Previous works [11,55,[65][66][67][68] showed that the supply of the air before the pump is the most efficient method to generate microbubbles. This aeration method is shown schematically in Figure 6.…”
Section: Pneumohydraulic Flotationmentioning
confidence: 99%
“…Speaking about pneumohydraulic systems, it is important to point out that the control of the air flow rate is important in order to provide the normal operation of the pump. It is recommended that air flow rate should be no more than 5-7% of water flow rate [65], and for special multiphase centrifugal pumps, the air flow rate should be in the range of 10-20% [80]. According to some researchers [54,55,102], the most effective microbubble generation occurs with an air flow rate ratio of 4-5%.…”
Section: Reliability and Simplicitymentioning
confidence: 99%
“…One of the most critical indicators of water quality in a water body is its dissolved oxygen concentration level [1]. In natural conditions, oxygen enters the water with wind, rain, splashing, and agitation of water from sources flowing into the water body due to the photosynthesis of aquatic plants [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…The oxygen demand of a water body ecosystem increases with the ingress of objects that require significant resources for decomposing by microorganisms in the bottom layer of water (e.g., polluted sewage, dust, fallen leaves) [4]. Decomposition produces carbon dioxide, organic substances like alcohol, and bad-smelling organic acids [1]. Increasing the efficiency of the decomposition process by adding oxygen to the water through aeration reduces the amount of nutrients for algae blooms and overly rapid plant growth.…”
Section: Introductionmentioning
confidence: 99%
“…Газовые эмульсии микропузырьков воздуха в жидкости находят применение в различных технологических процессах: при очистке сточных вод (прежде всего флотации [2]), в обогатительной промышленности, аквакультуре, медицине и др. На седиментационную устойчивость газовых эмульсий влияет скорость всплытия пузырька, которая зависит главным образом от диаметра пузырька, а также от разности плотностей газа и жидкости, вязкости среды и других параметров.…”
Section: Introductionunclassified